In situ Vaccination by Direct Dendritic Cell Inoculation: The Coming of Age of an Old Idea? - Castiello, Luciano; Aricò, Eleonora; D'Agostino, Giuseppina; Santodonato, Laura; Belardelli, Filippo (Frontiers in Immunology, 2019)
For more than twenty-five years dendritic cell (DC) based vaccination has flashily hold promises to represent a therapeutic approach for cancer treatment. While the vast majority of studies has focused on the use of antigen loaded DC, the intratumoral delivery of unloaded DC aiming at in situ vaccination has gained much less attention. Such approach grounds on the ability of inoculated DC to internalize and process antigens directly released by tumor (usually in combination with cell-death-inducing agents) to activate broad patient-specific antitumor T cell response. In this review, we highlight the recent studies in both solid and hematological tumors showing promising clinical results and discuss main pitfalls and advantages of this approach for endogenous cancer vaccination. Lastly, we discuss how in situ vaccination by DC inoculation may fit with current immunotherapy approaches to expand and prolong patient response.